Manuscript Catalogs and Inventories of Books from the Lands of the Grand Duchy of Lithuania – Some Problems of Publishing Rules - Kowkiel, Lilia; Pacevičius, Arvydas; Pietrzkiewicz, Iwona (Bibliotheca Lituana, 2012)
Historians and publishers of historical sources have a lot of problems with the texts written in different languages and alphabets, which were created at different times, in the multilingual areas inhabited by many nations following different religions. The historians of book culture have the same problems with texts of inventories and catalogues of books, which are the primary source of knowledge about the content of libraries. At present it’s also important the historical texts to be published in the digital form. This article is a part of the discussion on this very important subject.